Cerebrospinal fluid removal during spinal anaesthesia for caesarean delivery in a patient with idiopathic intracranial hypertension - Hasoon, Jamal; Urits, Ivan; Viswanath, Omar; Orhurhu, Vwaire; Munnur, Uma (Anestezjologia Intensywna Terapia, 2020)
Dear Editor, Idiopathic intracranial hypertension (IIH), also known as pseudotumour cerebri or benign intracranial hypertension, is a neurologic condition that commonly affects obese females of child-bearing age [1]. IIH occurs when cerebrospinal fluid (CSF) accumulates abnormally in the brain, leading to elevated intracranial pressure (ICP) and symptoms such as headache, papilloedema, and vision changes. This accumulation of fluid may be due to an increase in fluid production or a decrease in fluid absorption. It is characterised by an increased ICP without signs of altered mental status, absence of intracranial lesions, and normal CSF composition [2, 3]. The incidence of IIH is greatest in obese females of childbearing age, with an estimated incidence of 7.9/100 000 [1].